Sovereign Immunity: Chinese Views and Practices - Houli, Wang (Columbia Journal of Asian Law, 1987)
Since the establishment of diplomatic relations between the People’s Republic of China and the United States in 1979, the Sino-U.S. relationship has undergone substantial development. In the legal field, for example, a series of agreements have been reached on such diverse issues as nuclear energy cooperation, avoidance of double taxation, scientific and technical cooperation, and exploitation of marine resources. Over the past few years, the legal communities of both countries, including lawyers, judges, and law professors, have been exchanging visits with increasing frequency. Teachers and students from each country are teaching and studying in law schools and universities of the other. Lawyers have become increasingly involved in trade and economic transactions between the two nations. Increas- ing numbers of conferences, symposia, and seminars on legal and economic questions are being held jointly by scholars and practitioners from both countries. In short, legal ties between China and the United States have become stronger and broader than ever before.